PSVII-20 Heat stress alters reproductive phenotypic impacts of Zearalenone in pre-pubertal gilts - Roach, Crystal M (J Anim Sci, 2020)
Zearalenone (ZEA) is an estrogenic mycotoxin produced by strains of Fusarium and is often inadvertently consumed via feed contamination. Heat stress (HS) occurs when heat accumulation exceeds heat dissipation resulting in increased body temperature. Independently, HS and ZEA cause swine reproductive dysfunction such as delayed puberty onset, altered circulating steroid hormones and irregular estrous cycles. During HS, gilts become hyperinsulinemic and insulin regulates hepatic and ovarian chemical metabolism. We hypothesized that during HS, ZEA-induced alterations to reproductive parameters are heightened such that HS is additive to ZEA-induced reproductive toxicity. Prepubertal crossbred gilts (n = 38) were randomly assigned to six treatment groups: thermal neutral (TN) ad libitum fed controls (TNCT; n = 6); TN + ZEA (2 ppm; TNZ; n = 6); pair-fed (PF) control (PFCT; n = 6); PF + ZEA (2 ppm; PFZ; n = 6); cyclical HS control (HSCT; n = 7); and HS + ZEA (2 ppm; HSZ; n = 7) for 7 d. Ovarian and uterine weights (g) were measured, and nipple and vulva diameters (l × w; mm(2)) were assessed by digital calipers. Ovarian weight was decreased (P = 0.04) in the PFZ relative to PFCT, but ZEA did not affect ovarian weight in the other groups (P > 0.73). There was no impact of ZEA exposure on uterine weight (P > 0.22) or nipple diameter (P > 0.51) in any treatment groups, respectively. There was no effect of ZEA on vulva size in either of the TN groups; however, vulva diameter increased (P = 0.04) in the HSZ relative to HSCT. These data suggest that HS exaggerates some ZEA-induced phenotypic effects in prepubertal gilts. This project was supported by the Iowa Pork Producers Association.